Will variations in malaria prevalence due to climate change have clinical implications in the northern hemisphere?. Issue 6 (June 2016) - Belson, Elizabeth; Tyler, Carl
Abstract : Evidence‐based answer : No. Socioeconomic factors and disease control efforts will likely have a larger effect on spread than regional temperature variation. Because of this, malaria is unlikely to become a major health risk in North America (SOR: C, expert opinions).